Exchange traded funds and their association with the volatility of the daily returns of major South African banks - Herman, Barak (Department of Finance and Tax, 2025)
This dissertation examines whether the degree of ownership of major South African Bank shares by the Exchange Traded Fund (ETF) market in South Africa along with ETF's unique trading dynamics (for the purposes of this dissertation, “ETF's unique trading dynamics” refers to the relationship between ETFs and their constituent shares through the ETF share creation and redemption process and the purchase and sale of constituent shares), has an association with the volatility of the South African Major Bank's daily returns. This dissertation determines the degree of ownership by the ETF market and its trading dynamics using publicly available data through the identification and collation of publicly available data obtained from third-party data providers. Using a GARCH model process to estimate the volatility of daily returns, this dissertation then incorporates the degrees of ETF ownership and ETF trading dynamics variables as external regressors to assess whether there was a statistically significant association in explaining the volatility of daily returns of the Major South African Banks shares. The results of the dissertation are mixed. Concerning the degree of ETF ownership, there is evidence of a statistically significant negative association between the degree of ETF Ownership and the volatility of daily returns for two of the six shares, while in the instances of the remaining shares, there is no statistically significant association. With respect to ETF unique trading dynamics, driven by ETF-Specific Events (which, for the purposes of this dissertation, means the introduction of a new ETF into the market, the creation of new ETF shares, and redemption of existing ETF shares), no statistically significant association is found between the volatility of daily returns for any of the shares. This study reveals a nuanced relationship between ETF ownership and stock volatility in major South African banks, demonstrating that while higher ETF ownership may reduce volatility in some bank shares, its impact is not universal across the sector. These findings may be useful for investors, financial analysts and policymakers who are interested in understanding the potential impact ETFs may have on equity markets, and who may use this information for risk management, advising on investment strategies, and shaping regulations around ETFs. This research adds to the body of knowledge in relation to understanding of the role of ETFs in financial market stability and their potential impact on constituent share price volatility, with specific reference to emerging markets like South Africa, offering valuable insights for various market stakeholders.